Silent theater : the art of Edward Hopper - Wells, Walter; Hopper, Edward, 1882-1967.; Phaidon Press (London ; New York : Phaidon Press, 2007)
"Edward Hopper (1882-1967) is the greatest painter of American experience in the twentieth century. Hopper's enigmatic images speak to the modern world's deep concern with the human condition. In compositions that encompass the city and nature - ranging from theater interiors, hotels, restaurants, street scenes, railways and gas stations to landscapes and the sea - Hopper created a moving visual poetry. Indeed, Hopper's most celebrated paintings, such as Railroad Sunset, Early Sunday Morning and Nighthawks, have become world-famous icons of America's alternating sense of alienation and self-identity." "This monograph examines Hopper's art from diverse literary, psychological and cultural perspectives, yielding numerous fresh insights into his output. Detailed discussion of a wide array of Hopper's canvases, watercolors, etchings and meticulous sketches explores how the artist's troubled marriage, emotions and obsessive themes influenced his vision."--BOOK JACKET.
Hopper simplified --Raising the curtain --Vortices of despair --Sexual permutations --Women in doorways --The furtive eye --The naked and the nude --Variations at the window --Lust and longing --Cold embers --On track --Architectures --By the sea --Isles of refuge --E. Hopper, impresario.
Includes bibliographical references (pages 258-259) and index.
Keywords: Hopper, Edward, -- 1882-1967.; Artists -- United States -- Biography